2018
DOI: 10.31980/mosharafa.v7i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pedagogical Content Knowledge Mahasiswa Calon Guru Pada Program Studi Pendidikan Matematika

Abstract: Penelitian ini bertujuan untuk mengetahui pedagogical content knowledge mahasiswa calon guru pada program studi pendidikan matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Abulyatama Aceh. Untuk mencapai tujuan tersebut penelitian ini menggunakan pendekatan kualitatif dengan desain triangulasi, dimana peneliti mengumpulkan data dari beberapa sumber dan metode yang berbeda, membandingkan hasilnya dan menggunakan hasil temuan untuk melihat apakah saling memvalidasi satu sama lainnya. Data tentang ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
1
0
8
Order By: Relevance
“…Another study on mathematics students found that lecturing by implementing Valsiner's theory might convince them on probability courses (Tirto et al, 2019). In addition, the research on prospective teacher PCK that has been carried out previously is still limited to describing how the PCK of prospective teachers has not led to the learning of prospective teachers when teaching practice (Ayuningtyas & Apriandi, 2019;Gultom & Mampouw, 2019;Irfan et al, 2018;Makaraka et al, 2021). The novelty of this current study was that the author detected and described promoted action by prospective teachers when they had teaching practice in secondary school.…”
Section: Introductionmentioning
confidence: 92%
“…Another study on mathematics students found that lecturing by implementing Valsiner's theory might convince them on probability courses (Tirto et al, 2019). In addition, the research on prospective teacher PCK that has been carried out previously is still limited to describing how the PCK of prospective teachers has not led to the learning of prospective teachers when teaching practice (Ayuningtyas & Apriandi, 2019;Gultom & Mampouw, 2019;Irfan et al, 2018;Makaraka et al, 2021). The novelty of this current study was that the author detected and described promoted action by prospective teachers when they had teaching practice in secondary school.…”
Section: Introductionmentioning
confidence: 92%
“…Dua bagian besar yang membentuk PCK adalah content knowledge dan pedagogical knowledge (Irfan, Anzora, & Fuadi, 2018 Instrumen pengumpulan data yang digunakan adalah angket dan wawancara. Angket diberikan kepada subjek penelitian setelah mendapatkan pengarahan tentang ruang lingkup pembelajaran matematika daring dalam penelitian ini.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian terkait telah dilakukan oleh (Irfan et al, 2018;Malichatin, 2019;Supriyadi et al, 2018). Namun belum ada yang mengembangkan buku strategi pembelajaran matematika untuk anak sekolah dasar dimana dalam penggunaannya dapat menarik minat belajar peserta didik.…”
Section: Gambar 1 Hasil Ukg Tahun 2015unclassified